2004
DOI: 10.1111/j.1399-3038.2004.00140.x
|View full text |Cite
|
Sign up to set email alerts
|

Low vitamin D status is associated with low cord blood levels of the immunosuppressive cytokine interleukin‐10

Abstract: The cytokine interleukin-10 (IL-10) plays a pivotal regulatory role in tolerizing exogenous antigens. Experimental data indicate that low cellular availability of the vitamin D hormone 1,25-dihydroxyvitamin D [1,25(OH)2D] results in a down-regulation of IL-10 concentrations. The tissue production of an adequate amount of 1,25(OH)2D depends on a high circulating 25-hydroxyvitamin D (25-OHD) level. The present study was thus aimed at evaluating the associations between season of birth, vitamin D status, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
68
1
4

Year Published

2008
2008
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 88 publications
(76 citation statements)
references
References 32 publications
3
68
1
4
Order By: Relevance
“…At the molecular level, a link between vitamin D and IL-10 is evident. Human serum levels of pro-vitamin D correlate with those of IL-10 [13] and intact IL-10 signaling is essential for the vitamin D-mediated protection in murine experimental autoimmune encephalomyelitis [43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the molecular level, a link between vitamin D and IL-10 is evident. Human serum levels of pro-vitamin D correlate with those of IL-10 [13] and intact IL-10 signaling is essential for the vitamin D-mediated protection in murine experimental autoimmune encephalomyelitis [43].…”
Section: Discussionmentioning
confidence: 99%
“…Nutritional supplementation with the calcitriol precursor 25-hydroxyvitamin D 3 , leads to increased serum IL-10 levels in vivo [12]. Levels of 25-hydroxyvitamin D 3 in cord blood correlate to IL-10 levels and inversely to total IgE titers [13].…”
Section: Introductionmentioning
confidence: 99%
“…13,14 Inflammation caused by increased cytokines can affect glial cell functions and damage neurons. 15 Finally, 2 longitudinal studies have shown that vitamin D status at baseline is associated with the development of depression over time, suggesting that low vitamin D levels may predict the development of future depression.…”
Section: Discussionmentioning
confidence: 99%
“…There is also emerging evidence of neuroprotective roles for vitamin D through antioxidant pathways, enhanced nerve conduction, neurotransmitter targets, neuronal calcium regulation, and effects on inflammation. 6,[10][11][12][13][14][15] Emerging data suggest that elevated levels of proinflammatory cytokines in the brain may be associated with depression. 15 In human studies, an inverse correlation was found between vitamin D status and inflammation markers, and a positive correlation was found with anti-inflammatory cytokines For personal use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation